2013
DOI: 10.3748/wjg.v19.i17.2650
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and survival analysis of 837 Chinese colorectal cancer patients

Abstract: The overall survival of CRC patients has improved between 1996 and 2006. LNR is a powerful factor for estimating the survival of stage III CRC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
40
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 44 publications
11
40
1
1
Order By: Relevance
“…The result of this study is consistent with the finding of our study. In a study from China in 2013, the 3year survival rate was reported 0.74 (Yuan et al, 2013). The 5-year survival rate in our study (Yeole et al, 2001) and in Malaysia in 2010 (Ghazali et al, 2010), the 5-year survival rate was reported 33.6 and 34.3 respectively.…”
Section: Discussionsupporting
confidence: 39%
“…The result of this study is consistent with the finding of our study. In a study from China in 2013, the 3year survival rate was reported 0.74 (Yuan et al, 2013). The 5-year survival rate in our study (Yeole et al, 2001) and in Malaysia in 2010 (Ghazali et al, 2010), the 5-year survival rate was reported 33.6 and 34.3 respectively.…”
Section: Discussionsupporting
confidence: 39%
“…In most studies, the advanced age of patients with colorectal cancer, operated in emergency, was a risk factor (13)(14)(15), as in our study. Other studies have reported a poor prognosis in young patients with colorectal neoplasm.…”
Section: Discussionsupporting
confidence: 65%
“…Notably, despite the limitation of the sample size, tobacco exposure, diagnostic stage and the selected NKR genotypes were all found to be significantly associated with the number of metastatic lymph nodes, which is well known to be one of the most important prognostic factors in CRC (14,15). SNPs in receptor-encoded genes can affect a number of aspects of receptor function (16), and may also result in an increased susceptibility to disease or produce variable responses to therapeutic agents (17).…”
Section: Discussionmentioning
confidence: 99%